2018
DOI: 10.1158/1538-7445.am2018-2718
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2718: Preclinical development of humanized CD39 and CD73 blocking antibodies targeting the ATP/adenosine immune checkpoint pathway for cancer immunotherapy

Abstract: Within the tumor microenvironment, adenosine causes immune suppression and dysregulation of immune cell infiltrates resulting in tumor spreading. Adenosine accumulation results from the hydrolysis of extracellular immunoactivating ATP and ADP into AMP by the CD39 (ENTPD1) ectonucleotidase. AMP can be further hydrolyzed into immunosuppressive Adenosine (Ado) by CD73 (NT5E), a cell membrane ectonucleotidase of the NTPDase family.The immunosuppressive role of CD39 expressed on both Tregs and tumor cells has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Though highly variable, expression was also found on a limited number of NK cells isolated from mouse melanoma (SM1WT1) tumors (Young et al, 2018). Contrasting these reports is data by Perrot et al who reported no significant difference between CD73 expressed on circulating NK cells and those that have infiltrated tumors (Perrot et al, 2018). Collectively, this phenomenon has not been fully validated yet, is likely tumor-specific and requires further investigation.…”
Section: Expression Of Cd73 In Solid Tumorsmentioning
confidence: 77%
“…Though highly variable, expression was also found on a limited number of NK cells isolated from mouse melanoma (SM1WT1) tumors (Young et al, 2018). Contrasting these reports is data by Perrot et al who reported no significant difference between CD73 expressed on circulating NK cells and those that have infiltrated tumors (Perrot et al, 2018). Collectively, this phenomenon has not been fully validated yet, is likely tumor-specific and requires further investigation.…”
Section: Expression Of Cd73 In Solid Tumorsmentioning
confidence: 77%